Assessment of myometrial transcriptome changes associated with spontaneous human labour by high‐throughput RNA‐seq. Issue 3 (9th January 2014) - Chan, Yi‐Wah; van den, Hugo A.; Moore, Jonathan D.; Quenby, Siobhan; Blanks, Andrew M.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? In this study, we sought to survey the total transcript repertoire of human myometrium, comparing samples taken from patients at term who were not in labour with samples taken at term in spontaneous labour. These sequenced transcriptomes show the repertoire of possible proteins and their variants in myometrial smooth muscle, as well as transcriptional changes associated with term spontaneous labour. What is the main finding and its importance? We describe, for the first time, the transcriptome of the human myometrial samples taken from patients prior to and after the onset of spontaneous labour. We document a significant number of novel transcripts of both protein‐coding mRNA and microRNA. This information will be useful for the development of novel therapeutics and the formulation of new hypotheses to be tested by physiological experimentation. The transition of the human uterus from a quiescent to a contractile state takes place over a number of weeks. On such biological time scales, cellular phenotype is modified by changes in the transcriptome, which in turn is under the control of the underlying endocrine, paracrine, and biophysical processes resulting from the ongoing pregnancy. In this study, we characterize the transition of the human myometrial transcriptome at term from not in labour (NIL) to in labour (LAB) using high throughput RNA sequencing (RNA‐seq). RNA was isolated from the myometrium of uterine biopsies from patients at term who were not in labour (n = 5) and at term in spontaneous labour (n = 5) without augmentation. A total of 143.6 million separate reads were sequenced, achieving, on average, ∼13 times coverage of the expressed human transcriptome per sample. Principal component analysis indicated that the NIL and LAB transcriptomes could be distinguished as two distinct clusters. A comparison of the NIL and LAB groups, using three different statistical approaches (baySeq, edgeR, and DESeq), demonstrated an overlap of 764 differentially expressed genes. A comparison with currently available microarray data revealed only a partial overlap in differentially expressed genes. We conclude that the described RNA‐seq data sets represent the first fully annotated catalogue of expressed mRNAs in human myometrium. When considered together, the full expression repertoire and the differentially expressed gene sets should provide an excellent resource for formulating new hypotheses of physiological function, as well as the discovery of novel therapeutic targets.